CYTOTOXICITY OF AROMATIC COMPOUND FROM AN ENDOPHYTIC FUNGUS, CLADOSPORIUM SP. EN-S01 - Examinati, R. R. Indry Noviarin; Wulandari, Asri Peni; Putri Huspa, Desi Harneti; Andayaningsih, Poniah (International Journal of Current Pharmaceutical Research, 2018)
Objective: Endophytes have the potential to synthesize various bioactive secondary metabolites. The aims of the study were to isolate the major compound from endophytic Cladosporium sp. EN-S01., identify its function group, then evaluate its cytotoxicity. Methods: The endophytic fungus was grown in potato dextrose broth and extracted using ethyl acetate. Secondary metabolites were isolated by chromatographic separation and re-crystallization, and function group was determined by infrared spectroscopy. In vitro cytotoxicity was evaluated by the prestoblue assay. Result: The isolated aromatic compound evaluated by prestoblue assay against breast cancer cell line MCF-7 showed cytotoxicity with IC50 value of 746,03 ppm. Conclusion: Our findings indicate this aromatic compound might be useful lead compounds to develop cytotoxic drugs.